Occurrence of Side Effects from Anti-Tuberculosis Drugs in Urban Nepalese Population under DOTS Treatment - Koju, Dinesh; Rao, B.S.; Shrestha, Bhawana; Shakya, Rajani; Makaju, Ramesh (Kathmandu University Journal of Science, Engineering and Technology, 2005)
Tuberculosis is one of the foremost public health problems causing an enormous burden of suffering and deaths. Chemotherapy is the basic approach to clinical tuberculosis control. 1Essential anti-tuberculosis drugs are Isoniazide (INH), Rifampicin (RMP), Pyrazinamide (PZA), Ethambutol (E) and Streptomycin (S). Department of Pharmacy, KU, KUTH, and Dhulikhel conducted this study in collaboration with German-Nepal Tuberculosis Project (GENETUP) and Korea-Thimi Friendship Hospital during March 2005 to July 2005. Total 70 newly diagnosed pulmonary or extra-pulmonary tuberculosis patients were included in the present study. Patients were kept under observation during whole treatment period. Clinical, hematological and biochemical monitoring form the basis of diagnosing side effects due to anti-tuberculosis therapy. Among the 70 cases studied, 70% were male and 30% were female. There was significant increase in the bilirubin total, bilirubin direct, AST, ALT, alkaline phosphatase, eosinophils, lymphocytes, monocytes after anti-tuberculosis treatment whereas there was significant decrease in WBC count, neutrophils, platelets count, and ESR after anti-tuberculosis treatment. Serum level of creatinine was normal before and after anti- tuberculosis treatment. In our study, slight increase in uric acid level was detected after anti- tuberculosis treatment when compared to pretreatment, though it was in the normal range. Of the 70 patients treated for tuberculosis, 80% of the total number of patients reported at least one type of side effects. 24 patients (34.29%) had experienced major side effects. 8 elderly patients (44.44%) and 16 younger patients (30.76%) had experienced major side effects. Female gender (38.10%), alcoholics (38.89%) and sputum-smear positive (32.14%) were associated with increased occurrence of major side effects. The overall side effects indicate that side effects are not to be neglected. It was experienced that timely detection and temporary withdrawal of the offending agent can completely cure anti-tuberculosis drugs- induced side effects. For this, careful patient monitoring clinically, hematologically and biochemically especially during first few weeks of chemotherapy and patient counseling regarding side effects of the anti-TB medications are necessary.